2020
DOI: 10.3390/agriculture10090389
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the PAL Enzymatic Activity and Polyphenolic Compounds in Leaves and Fruits of Two Myrtle Cultivars during Maturation

Abstract: The leaves and berries of myrtle (Myrtus communis L.) are rich in phenolic compounds, such as phenolic acids, flavonoids, and flavanols. The richness of these antioxidant compounds allows the potential use of myrtle biomasses as raw materials for medicinal and functional food products. Most of the phenolic compounds originate from the phenylpropanoid pathway, where phenylalanine ammonia lyase (PAL) enzyme activates the first step. The objective of this research is to study the activity of PAL as related to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…It is generally considered that the browning sensitivity of fresh‐cut slices is a consequence of the complex interaction of browning‐related enzymes and phenolic compounds (Cantos et al., 2002; Kasnak, 2020; Piližota & Sapers, 2010). PAL involves in phenolic biosynthesis and can be induced by processing operations (Medda et al., 2020). High PAL activity generally induces the consequent accumulation of phenolic compounds (Chisari et al., 2007; Jeong et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that the browning sensitivity of fresh‐cut slices is a consequence of the complex interaction of browning‐related enzymes and phenolic compounds (Cantos et al., 2002; Kasnak, 2020; Piližota & Sapers, 2010). PAL involves in phenolic biosynthesis and can be induced by processing operations (Medda et al., 2020). High PAL activity generally induces the consequent accumulation of phenolic compounds (Chisari et al., 2007; Jeong et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with Song et al [ 21 ], who mentioned that Zn treatments enhanced the accumulation of anthocyanins in berry skin, and Hashemi et al [ 56 ], who explained the role of ZnO nanoparticles in increasing anthocyanin production in soybean. Additionally, Wadhwa et al [ 51 ] mentioned that Zn served as a co-factor for PAL enzyme activity and Medda et al [ 12 ] advocated that Zn played a regulatory enzyme during fruit ripening for flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Various reasons for inferior color development in table grapes have been reported for the conditions prevalent in Egypt, such as high temperature [ 8 , 9 ]) and vigorous growth with dense, shaded canopies [ 10 , 11 ]. The dynamics of anthocyanins and enzyme phenylalanine ammonia-lyase (PAL) activity suggested that PAL is an essential enzyme for their biosynthesis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several studies [ 16 , 17 , 18 , 19 ] on the phenolic profile of myrtle leaves and berries, as well as their biological properties—e.g., their antioxidant activity—to the best of our knowledge, there is no information available about the biosynthesis at the gene expression level. Currently, only studies of the phenylalanine ammonia lyase (PAL) enzymatic activity during the development of berries and leaves in dark-blue and white myrtle cultivars have been carried out [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detected flavanols with the highest amounts were myricetin 3-galacatoside (183.1 mg/100 g dry weight) and myricetin 3-rhamnoside (135.57 mg/100 g dry weight). Regarding the quantitative composition of the phenolic compounds found in a previous study, at ripening, the “Giovanna” cultivar showed a lower content of total phenolic compounds than the “Grazia” cultivar (37 and 46 mg gallic acid equivalent (GAE)/g DW for “Giovanna” and “Grazia”), as well as a lower content of total tannins (0.33 mg catechin equivalent (CE)/g DW for “Giovanna” and 2.73 mg CE/g DW for “Grazia”) [ 27 ]. From the perspective of genetic diversity, both cultivars have been evaluated using ISSR (Inter simple sequence repeat) and AFLP (Amplified fragment length polymorphism) molecular marker analyses.…”
Section: Introductionmentioning
confidence: 99%